Poslat ću ti što ti srce bude htjelo. Iva Pleše, Pismo, poruka, mejl: etnografija korespondencije. - Pleša, Izabela (Anafora, 2022)
Poslat ću ti što ti srce bude htjelo. Iva Pleše, Pismo, poruka, mejl: etnografija korespondencije.